Bisphenol A exposure induces multiple effects in DOPC membrane models - Maximino, Mateus D. [UNESP]; Martin, Cibely S. [UNESP]; Aléssio, Priscila [UNESP] (Elsevier, 2022)
Due to its now well-known endocrine-disrupting behavior, Bisphenol A (BPA) has focused on many interactions, detection, and removal studies in the last few years. The application of simple membrane models to identify specific interactions in some regions of the cells, such as the membrane, is essential to help understand the aspects of the mechanisms of action. This work evaluated the effects of the BPA exposure over membrane models of a fluid phospholipid, the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC). The BPA interaction with the DOPC monolayers was performed using Langmuir films, evaluating changes in π-A isotherms, lipid fluidity, and interaction at the molecular level by PM-IRRAS spectroscopy. Giant unilamellar vesicles (GUVs) were used to reveal alteration in the shape and morphology of the lipid bilayers promoted by BPA. Multiple effects were observed in the GUVs, including surface fluctuations, an endocytosis-like effect, the formations of budding, and scissions. These alterations could be related to changes observed in the phosphate groups of DOPC in the PM-IRRAS analysis and the lipophilic properties of BPA. Furthermore, the changes observed indicate that BPA has an affinity to the membrane, which could lead to different implications or effects in cells not yet understood, which requires further investigations.
Keywords: Bisphenol A; Cell membrane models; Langmuir monolayers; Morphology changes; Vesicles